2022
DOI: 10.3390/polym14030449
|View full text |Cite
|
Sign up to set email alerts
|

Metal Complexes of the Porphyrin-Functionalized Polybenzoxazine

Abstract: New porphyrin-functionalized benzoxazine (Por-BZ) in high purity and yield was synthesized in this study based on 1H and 13C NMR and FTIR spectroscopic analyses through the reduction of Schiff base formed from tetrakis(4-aminophenyl)porphyrin (TAPP) and salicylaldehyde and the subsequent reaction with CH2O. Thermal properties of the product formed through ring-opening polymerization (ROP) of Por-BZ were measured using DSC, TGA and FTIR spectroscopy. Because of the rigid structure of the porphyrin moiety append… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 63 publications
(71 reference statements)
1
9
0
Order By: Relevance
“…The FT-IR spectra show that the peaks of the porphyrin skeleton are located at 1598, 1354, and 798 cm –1 , and the peaks at 3354 and 3440 cm –1 are absorption bands of NH 2 units (Figure b) . For Co-TAP, the peak related to N–H in-plane bending vibration at 959 cm –1 disappears, and a new signal at 991 cm –1 appears, confirming the incorporation of Co ions into the center of the macrocycle . This evidence persuasively proved the incorporation of cobalt ions into the porphyrin structures and the successful synthesis of the desired structures.…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…The FT-IR spectra show that the peaks of the porphyrin skeleton are located at 1598, 1354, and 798 cm –1 , and the peaks at 3354 and 3440 cm –1 are absorption bands of NH 2 units (Figure b) . For Co-TAP, the peak related to N–H in-plane bending vibration at 959 cm –1 disappears, and a new signal at 991 cm –1 appears, confirming the incorporation of Co ions into the center of the macrocycle . This evidence persuasively proved the incorporation of cobalt ions into the porphyrin structures and the successful synthesis of the desired structures.…”
mentioning
confidence: 67%
“…Compared with the TAPP, the maximum absorption of Co-TAP at 444 nm presents a slightly red shift of 16 nm. Additionally, when porphyrinic macrocycle is coordinated with Co ions, the Q band pattern is simplified to two Q bands at around 555 and 605 nm, which is attributable to the more symmetrical environment . The FT-IR spectra show that the peaks of the porphyrin skeleton are located at 1598, 1354, and 798 cm –1 , and the peaks at 3354 and 3440 cm –1 are absorption bands of NH 2 units (Figure b) .…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…It is expected that the introduction of melamine, which has an active amino and triazine structure, can enhance the thermal stability and crosslink density of polymers 46 . Also, it was found that the introduction of Schiff‐base structure could enhance the crosslink density and stability of the resin 47–52 . As the report by Xu, 49 two diepoxides containing a two‐benzene‐ring‐conjugated Schiff base when cured with an aromatic diamine result in high‐performance thermosets.…”
Section: Introductionmentioning
confidence: 95%
“…Its polymeric product can form through thermal ring-opening polymerization (ROP) without the need to add any potentially harmful catalysts (Scheme S1). Holly and Cope prepared the first monofunctional BZ, 3,4-dihydro-2 H -1,3-benzoxazine, through Mannich condensation . Although the chemical structures of PBZs are similar to those of traditional phenolic resins, PBZs are generally prepared by using simple and self-catalyzed polymerization processes and display good heat resistance, high degradation and glass transition ( T g ) temperatures, near-zero volumetric shrinkage during polymerization, excellent flame retardancy, good mechanical properties, low dielectric constants, water absorption properties, and variable surface free energies. , In addition, high flexibility in the molecular design of BZ resins allows a variety of physical and mechanical properties to be introduced into the resulting PBZ materials. Moreover, the properties of PBZs lead to many potential applications in, for example, adsorbents, metal capture, energy storage, gas uptake, shape-memory and self-healing polymers, anticorrosion coatings, adhesives, and electronic materials. The syntheses and characteristics of mono-, bi-, tri-, and tetrafunctional BZs have been investigated in detail by many research groups. ,,,,,,, In general, monofunctionalized BZs tend to form linear polymers of relatively lower molecular weight, while bifunctional BZs form cross-linked macromolecules featuring more stable networks …”
Section: Introductionmentioning
confidence: 99%